Prevalence of COVID-19 Among 8000 Patients at a Hospitalized and Mortality in Old Age - de Godoy, Maria R. P.; Salomão, Maria Lucia Machado; Queiroz, Flavia; de Godoy, Jose Maria Pereira (Current Aging Science, 2024)
Background: COVID-19 created a general challenge to healthcare systems throughout the world and was an important cause of mortality. Aim: The aim of the present study was to report the general evolution of patients with COVID-19 at a teaching hospital and analyze differences by age group and sex considering mortality rates in the years 2020 and 2021 among patients older than 60 years of age. Methods: A cross-sectional study was conducted with patients hospitalized with a diagnosis of COVID-19 confirmed by RT-PCR at the São Jose do Rio Preto university hospital between March 2020 and March 2022. The patients were male and female patients, of varying ages belonging to the region of Sao Jose do Rio Preto, were accommodated in the wards or intensive care units (ICUs). Overall mortality was analyzed for the hospital as well as in the ICUs and wards. This analysis was performed separately in two years considering age group, sex, and main comorbidities in patients older than 60 years of age. Results: A total of 8032 patients with COVID-19 were hospitalized between March 2020 and March 2022: 2866 patients with 658 deaths (22.92%) in 2020; 4324 patients with 1168 deaths (27.01%) in 2021; and 842 patients with 205 deaths (24.35 %) in 2022 up to the month of March. More than half (53.60%) of the patients were hospitalized in the ICUs and 46.39% were hospitalized in the wards. Differences in the mortality rate were found for the different age groups in the comparison of the years, with more deaths occurring among individuals up to 90 years of age in the second year (p <0.05). Men were affected more and had a higher mortality rate (p <0.0001). The main comorbidities were cardiovascular disease (70.93%), diabetes (37.76%), and obesity (23.68%). Conclusion: The mortality rate of older people hospitalized with COVID-19 was higher than the average, it was higher in 2021 compared to 2020 and increased with age. Cardiovascular disease, diabetes, and obesity were the main comorbidities.
Keywords: old age